Feasibility of a 109Cd-based portable XRF device for measuring skin iron concentration in anaemic and β−Thalassaemic patients. (1st November 2022) - Bangash, Sami Ullah Khan; McNeill, Fiona E; Farquharson, Michael J; Chettle, David R
Abstract: Iron is an essential element vital for growth and development. The severe effects on the body due to iron deficiency or overload have prompted sustained research into accurate in vivo iron measurement techniques for the past several decades. X-ray fluorescence (XRF) analysis of iron in the body has been investigated in this work because of the non-invasive nature of the technique. A system has been designed using a silicon drift detector to measure the low-energy iron K α x-rays excited in the samples by the silver x-rays from 109 Cd of energy 22 keV and 25 keV. The source is contained within a tantalum shielding cap designed to reduce the spectral background. The system was calibrated against 3D printed polylactic acid (PLA) phantoms filled with solutions of iron at various concentrations. The iron x-ray signals were normalized to a nickel x-ray signal which improved the system's reproducibility. The 3D phantoms and normalisation resulted in a linear calibration line (p < 0.001 and r 2  > 0.999). For a real-time measurement of 1800 s, the minimum detectable limit for the system was measured to be 1.35 ± 0.35 ppm which is achieved with a low radiation dose of 1.1 mSv to the skin surface. This low detection limit and low dose mean the system is feasible for application to human measurements in both iron deficiency and overload disease. The system will proceed to post-mortem validation studies prior to in vivo system efficacy testing.